Inside Cover: Electrogenerated Chemiluminescence of Semiconductor Nanoparticles and Their Applications in Biosensors (ChemElectroChem 7/2017). Issue 7 (21st June 2017) - Benoit, Lora; Choi, Jai‐Pil
Abstract : The Inside Cover picture is an illustration to describe the photoluminescence (PL) and electrogenerated chemiluminescence (ECL) processes of semiconductor nanoparticles and their biosensing applications. More details can be found in the Minireview by L. Benoit and J.‐P. Choi onpage 1573 in Issue 7, 2017 (DOI:10.1002/celc.201700219 ).